A study of the effects of thematic language teaching on the promotion of multimedia design students’ listening and speaking skills - Yin, Sheng-Kai (Frontiers in Psychology, 2022)
Previously, language teaching has been focused on the passive learning of the alphabet. In addition, the research on teaching listening and speaking skills was limited. Listening skill is the key to learning a language, and speaking is the first explicit behavior of language. In order to improve language skills which are emphasized in new curriculum guidelines, student-centered thematic language teaching is considered as valuable. Through this, the concepts of multiple intelligences and curriculum integration were re-emphasized. An experimental design was adopted in the current study. This study was conducted with the participation of 224 students from the Department of Multimedia Design in universities in the south of Taiwan. The research data were collected between September 2021 and December 2021. The implementation process took 16 weeks (a total of 48 h) of thematic language teaching. The research results revealed 1. significant positive effects of thematic language teaching on listening, 2. significant positive effects of thematic language teaching on speaking skill, and 3. significant negative effects of thematic language teaching on learning anxiety. According to the results, it is expected that this study can help multimedia design students improve their listening and speaking skills as well as core language skills.